Audit Committee Chair’s Legal Expertise and Real Activities Manipulation: Empirical Evidence from Malaysian Energy and Utilities Sectors - Ghaleb, Belal Ali Abdulraheem; Al-Duais, Shaker Dahan; Hashed, Abdulwahid Ahmed (International Journal of Energy Economics and Policy, 2020)
Recent studies claim that improvements in regulations and corporate governance law in different countries are restricting accrual-based earnings management and encouraging managers to shift to real earnings management (REM). However, it is not yet clear whether audit committee directors with legal expertise are associated with higher or lower REM. Thus, this study aims to investigate the relationship between the audit committee (AC) chair’s legal expertise and REM in the energy and utilities sectors in Malaysia. The study uses a sample of all energy and utilities companies listed on Bursa Malaysia between 2013 and 2018. Ordinary least squares (OLS) regression is applied to analyse the study data. The study finds that AC chairs with legal expertise are positively and significantly associated with REM, suggesting that they have not yet ceased REM practices. The findings add to the corporate governance and earnings management literature, and inform regulators and other readers of financial reports about the monitoring role of the AC chair. Keywords: Real earnings management, audit committee chair, legal expertise, corporate governance, emerging market. JEL Classifications: M21, G34, M41, M42 DOI: https://doi.org/10.32479/ijeep.10258